EFEKTIVITAS PENDEKATAN CULTURALLY RESPONSIVE TEACHING BERBANTUAN ¬E-LKPD DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SMP - Jaka Wisnu Wardana; Sugiyanti; Lilik Ariyanto; Purwanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The learning process influences the learning outcomes of students, so it is necessary to have learning that suits the needs of students. This study aims to determine the effectiveness of the CRT approach to learning outcomes on quadratic function material. This research is a quantitative research. The samples in this study were students of class IX SMP N 6 Semarang, class IX B as the experimental class and IX D as the control class. Data were obtained based on posttest scores, with the experimental class learning completeness test results 87.5%. The difference test of learning outcomes obtained which is 0.027 < 0.05, so there is a difference in the average learning outcomes. The results of the simple linear regression test obtained R = 0.518 and R2 = 0.269 and , namely 3.321> 2.042 so that there is a positive influence between learning activeness and learning outcomes.